Gut microbiota and metabolites in estrus cycle and their changes in a menopausal transition rat model with typical neuroendocrine aging - Dai, Ruoxi; Huang, Jianqin; Cui, Liyuan; Sun, Ruiqi; Qiu, Xuemin; Wang, Yan; Sun, Yan (Frontiers in Endocrinology, 2023)
Background Neuroendocrine alterations in the mid-life hypothalamus coupled with reproductive decline herald the initiation of menopausal transition. The certain feature and contribution of gut microflora and metabolites to neuroendocrine changes in the menopausal transition remain largely unknown. Methods Fecal samples of rats experiencing different reproductive stages were collected and processed for 16S rRNA and liquid chromatography–mass spectrometry sequencing. The differences of gut microbiota and metabolites between young and middle-aged rats during proestrus and diestrus were analyzed, and their relationships to neuroendocrine aging were then examined. Results At the genus level, Anaeroyorax, Rikenella, Tyzzerella_3, and Atopostipes were abundant at proestrus, while Romboutsia, Turicibacter, Clostridium_sensu_stricto_1, Ruminococcaceae_NK4A214_group, CHKCI002, Ruminococcaceae_UCG-010, Staphylococcus, Family_XII_AD3011_group, Ruminococcaceae UCG-011, and Christensenellaceae_R_7_group were enriched in the diestrus of middle-aged rats. DNF00809, Phocea, and Lachnospiraceae_UCG-006 were found abundant during proestrus instead, while Bacteroides, Lactobacillus, Erysipelatoclostridium, Anaeroplasma, Anaerofustis, Parasutterella, and Enterococcus were enriched at the diestrus of young female individuals. Discriminatory metabolites were identified involving 90 metabolic pathways among the animal sets, which were enriched for steroid hormone biosynthesis, arachidonic metabolism, primary bile acid synthesis, and ovarian steroidogenesis. A total of 21 metabolites lacking in hormone-associated changes in middle-aged female individuals presented positive or negative correlations with the circulating luteinizing hormone, bile acid, fibroblast growth factor 19, and gut hormones. Moreover, close correlations were detected between the intestinal bacteria and their metabolites. Conclusion This study documents specific gut microbial composition changes and concomitant shifting trends of metabolites during menopausal transition, which may initiate the gut–brain dysfunction in neuroendocrine aging.